1998
DOI: 10.1017/s1357729800008833
|View full text |Cite
|
Sign up to set email alerts
|

Differential response of dairy cows to supplementary light during increasing or decreasing daylength

Abstract: Two experiments were conducted to compare the response oflactating cows to supplementary light in their lying area during increasing and decreasing natural daylength. During decreasing daylength, supplementary light in the lying area increased the time cows spent lying down and considerably reduced calculated food intake, milk production, live weight and body condition, so that lights were installed in the feeding area for the last half of the experiment, which partially restored intake and live weight. Plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…It has also been observed that the reduction of the daylight in autumn caused a compression of grazing time to within daylights hours (Phillips and Leaver, 1985). In the present experiment, artificial light of the barn was off during the night between 2030 and 0630 h, but it has been observed that artificial light during the night had limited impact of the daily pattern of chewing behavior of dairy cows (Tanida et al, 1984), at least when day length is increasing (Phillips et al, 1998). It is possible that the absence of vision during the night deterred the animals from grazing outside but other external factors, such as temperature or solar radiation, can significantly alter chewing behavior at grazing compared to indoor feeding (Prasanpanich et al, 2003).…”
Section: --mentioning
confidence: 58%
“…It has also been observed that the reduction of the daylight in autumn caused a compression of grazing time to within daylights hours (Phillips and Leaver, 1985). In the present experiment, artificial light of the barn was off during the night between 2030 and 0630 h, but it has been observed that artificial light during the night had limited impact of the daily pattern of chewing behavior of dairy cows (Tanida et al, 1984), at least when day length is increasing (Phillips et al, 1998). It is possible that the absence of vision during the night deterred the animals from grazing outside but other external factors, such as temperature or solar radiation, can significantly alter chewing behavior at grazing compared to indoor feeding (Prasanpanich et al, 2003).…”
Section: --mentioning
confidence: 58%
“…2 in morning-fed EP heifers on day 163. Phillips et al (1998) suggested that the response of cattle to photoperiod may depend more on changes in photoperiod than photoperiod per se. Subsequent to the first month of our experiments, while the duration of photoperiod was longer for the EP than NP treatment, the duration of photoperiod was rising approximately 2.5-fold more rapidly in NP than EP treatments (Fig.…”
Section: Prolactinmentioning
confidence: 99%